(untitled) (Economics and region, 2024)
The utilisation of contemporary market resources is solely intended to enhance profitability and competitiveness. The topic is of great relevance to the production process, as labour resources represent a significant factor in this area. Indeed, without such resources, any company activity is rendered impossible. The quality of the company’s products is satisfactory, and the company is unable to function without a sufficient supply of spare products. It is more challenging to manage an actual enterprise than it is to manage physical and human capital and labour resources. Production elements and labour resources, despite physical illnesses, play a crucial role in improving product quality and maintaining resources in all parts of the company’s production and business operations. The efficiency of the utilisation of energy resources derived from the labour system within the enterprise is reflected in fluctuations in labour productivity. The measurement of labour productivity serves as a general indicator of economic activity among various subjects within the modern economic landscape. This management approach presents a comprehensive representation of the case, encompassing its strengths and limitations. Labour productivity enables the drawing of conclusions regarding the performance of individual employees or the enterprise as a whole. In order to ascertain whether the consumption of food per unit of time is optimal and whether the ratio of the working employee to the enterprise’s income is reasonable, it is necessary to develop food productivity. The term "labour productivity" can be applied at the individual, local or social level. The term "individual" denotes the labour productivity of an employee, whereas "local" signifies the average result for an enterprise or industry. The social measure is calculated on the basis of the entire employed population and is analogous to the ratio of the total number of jobs in the production of the gross product. Concurrently, the productivity of labour that has become materialised represents one of the driving forces behind effective labour productivity growth. Consequently, it serves as the foundation for the development strategy of its respective industry. Furthermore, productivity is defined as an integrative, multi-factorial concept that assesses the quality of products, the qualifications of personnel, the level of technology and the level of management, the socio-economic potential of marketing and management, the utilisation of creative and innovative factors as a tool (material and financial resources). In order to enhance labour productivity, it is essential to enhance personnel management, obtain information regarding forthcoming expenditure, recruit new personnel, devise compensation for dismissal, facilitate training and qualifications, and establish a bonus fund. The ultimate objective of predictive analysis is to enhance labour productivity. Productivity is the primary source of genuine economic growth and advancement. In order to maintain the standard of living of employees of competitive, including international, security organisations, it is essential to achieve a competitive level of productivity.